Partisipasi Masyarakat Dalam Perencanaan Pembangunan Program SANIMAS (IsDB) Di Kelurahan Tanjung Gusta Kota Medan - Julpian Harahap; Muhammad Rizki Nasution (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara Medan, 2020)
Community participation at Tanjung Gusta Medan in the SANIMAS development program by reviewing the performance of BKM, KSM, and IsDB. Overview of socialization and drawn by society; The establishment of the BKM Community Health Service Agency and the KSM community NGO as well as the form of community participation in the implementation of sanitation and promotion of sanitary in the village of Tanjung Gusta and the role of government in creating participation in the process of socialization and promotion of the sanitation level of Tanjung Gusta Medan Helvetia, Medan. The qualitative approach became the process of drafting this research by combining observation methods and interviews to get results. The role of BKM and KSM in public socialization participation in Sanimas is well done. The community also still relies on the field facilitator's Tanaga (TFL) as a mentor in running the program